Conveniência e plausibilidade da proposição de que justiça é harmonia n A República de Platão - Lima, Jorge dos Santos (2013)
This thesis endorses the interpretation that in Plato`s Republic the argument made by Thrasymachus in which justice is the convenience of the most powerful one is implicitly accepted by Socrates. Although Thrasymachus´ discussion does not show any similarity with the argument of Socrates, it proposes a sarcastic and ironic comment on political life. Socrates accepts this comment to develop a more refined notion of the category of the most powerful ones. While Thrasymachus assumes that the convenience of the most powerful ones includes the power to subordinate all and everything to their individual pleasures, Socrates admits that the most powerful ones are defined only by their characteristic of being able to hold power in perpetuity. In this context, the main theme of The Republic is that the harmony between the functional classes of the city is convenient for perpetual power. For preservation of harmony, the functional class of the most powerful considers the convenience of forsaking a possible monopoly on pleasure towards a redistribution that promotes harmony, which also makes it convenient for the other classes. Thus, we can explicitly say that the most powerful ones believe in a sense of justice as convenience for everyone, but implicitly believe only in the argument that justice is what is convenient for themselves. Since convenience is what promotes harmony between functional classes, it becomes convenient to Socrates to believe that the understanding justice that the most powerful ones have is not publicly disclosed. The notion that all the speculation of the dialogue between the characters cannot be true, but, at best, only plausible and convenient is also part of the central argument in The Republic. Socrates needs to modify the nature of the functional classes through a targeted program of sexual reproduction and a program of ideological indoctrination so that the proposal to promote harmony through the elements of the city, declaring that justice is in favor of the weakest becomes a more plausible and convenient speech. To make the new system more plausible, Socrates develops a metaphysics based on the mathematical notion of harmony, such metaphysics serving the official rhetoric of the political regime presented by Socrates